Optimization of Flight Routes Employing the Simulated Annealing Method in the Context of the Indonesian National Airline Industry - Juniawan, Singgih; Roysen, Uti; Alam, Fachrul; Zainuddin, Zafitri; Daruki, Daruki; Taher, Hermawan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This research was conducted in the context of significant air traffic growth in Indonesia, where the increasing number of passengers each year presents an opportunity for airlines to expand their route networks and reach more markets. To seize this opportunity, a national airline based in Jakarta conducted internal research to open new flight routes connecting several important cities in Indonesia, namely Jakarta, Kupang, Pangkal Pinang, Pekanbaru, Makassar, and Banjarmasin.This research aims to obtain an optimal flight route that can enhance the effectiveness and efficiency of the planned airline routes. The research utilizes the Simulated Annealing-Traveling Salesman Problem optimization method to achieve this objective. This method is employed to find the best solution in determining the shortest route that includes visits to each destination city.The initial proposed flight route by the airline was Banjarmasin-Pangkal Pinang-Pekanbaru-Jakarta-Kupang-Makassar, with a total distance of 5,127 km. However, the research yielded a different optimal flight route after conducting the optimization process using the Simulated Annealing-Traveling Salesman Problem method. The discovered optimal flight route is Pekanbaru-Pangkal Pinang-Jakarta-Banjarmasin-Makassar-Kupang, with a total distance of 3,256 km. A comparison between the initial and optimal routes reveals that the new route has a 36.49% shorter distance than the initial route.